Is a Single-Dose, Single-Agent Perioperative Antibiotic Protocol Adequate for Endoscopic Endonasal Skull Base Surgery? A 10-Year Review of 422 Cases - Hughes, Mark A.; Phillips, Nick; Tyagi, Atul; Sheikh, Asim; Sethi, Kavita; Nix, Paul (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Postoperative meningitis is a rare but potentially fatal complication of endoscopic endonasal skull base surgery. Prophylactic antibiotic use varies considerably worldwide. We sought to analyze the safety of a single-agent, single-dose protocol.Design, Setting, and Participants A retrospective review of 422 procedures performed during 404 admission episodes from 2009 to 2019, encompassing sella, parasella, and other anterior skull base pathologies.Main Outcome Measures Primary outcome measure was development of meningitis within 30 days of surgery. Additional information collected: underlying pathological diagnosis, intraoperative cerebrospinal fluid (CSF) leak, postoperative CSF leak, and primary or revision surgery.Results Of 404 admission episodes for endoscopic anterior skull base surgery, 12 cases developed meningitis. Seven had positive CSF cultures and all 12 recovered. For pathology centered on the sella (including pituitary adenoma), the rate of meningitis was 1.1% (3/283). For pathologies demanding an extended approach (including meningioma and craniopharyngioma), the rate of meningitis was 14.5% (9/62). Postoperative CSF leak requiring surgical repair increased the relative risk by 37-fold. There were no cases of meningitis following repair of long-standing CSF fistula or encephalocoele (0/26) and no cases following surgery for sinonasal tumors with skull base involvement (0/33).Conclusion For sella-centered pathologies, a single dose of intravenous co-amoxiclav (or teicoplanin) is associated with rates of meningitis comparable to those reported in the literature. Postoperative meningitis was significantly higher for extended, intradural transphenoidal approaches, especially when postoperative CSF leak occurred. Fastidious efforts to prevent postoperative CSF leak are crucial to minimizing risk of meningitis.
Keywords: endoscopic; endonasal; skull base; meningitis